Born under a lucky star: Financial aid, college completion, labor supply, and credit constraints - Jeffrey T. Denning (W.E. Upjohn Institute for Employment Research, 2017)
Higher education has experienced many changes since the 1970s, including an increase in the price of college, an increase in student employment during college, a decrease in college completion rates, and an increase in time to degree. This paper ties these trends together by causally linking changes in financial aid with time to degree and student employment during college. I find that additional financial aid accelerates graduation for university seniors because they increase credits attempted and reduce earnings while in college. In reaching this finding, I use administrative education and earnings data to examine a discrete change in the amount of federal financial aid available to financially independent students. The estimates in this paper imply that roughly 50 percent of the observed increase in time to degree can be explained by changes in tuition.
Keywords: I22; D14; H52; 330; financial aid; labor supply; college completion